Novel type 4 secretion system (T4SS)-related genes of Edwardsiella tarda (Orinoquia, 2015)
Edwardsiella tarda is a Gram-negative bacterium that causes edwardsiellosis, a disease of fish and mammals including humans and characterized by multiple abscesses. Different strains of E. tarda possess a number of virulence, antibioticresistance, and toxin secretion system-related genes that explain in some extent its capacity to survive within phagocytic cells and to infect a variety of hosts. Previously we introduced a virulent E. tardastrain (ETSJ54) isolated from Japanese flounder (Paralichthys olivaceus) with edwardsiellosis and reported a number of virulence-related genes. In this study we have re-analyzed the sequencing data of ETSJ54 and identified novel type IV secretion system-related genes, most of them were flanked by transposase and plasmid encoding genes. Interestingly, their nucleotide sequence had no identity to those of the genes published in the E. tarda EIB202 genome, a virulent strain isolated from turbot (Scophthalmus maximus) in China. The results suggest differences in gene content between geographically distinct E. tarda strains that may encourage additional E. tarda genome sequencing projects.Keywords: Pathogenesis; T4SS genes; Virulence.
Keywords: Pathogenesis; T4SS genes; Virulence